2007
DOI: 10.1007/s00213-007-0974-x
|View full text |Cite
|
Sign up to set email alerts
|

The mGlu2 but not the mGlu3 receptor mediates the actions of the mGluR2/3 agonist, LY379268, in mouse models predictive of antipsychotic activity

Abstract: The mGlu2 but not the mGlu3 receptor subtype mediates the actions of the mGluR2/3 agonist, LY379268, in mouse models predictive of antipsychotic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
147
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(168 citation statements)
references
References 32 publications
(35 reference statements)
20
147
1
Order By: Relevance
“…Furthermore, mGlu2 receptor knockout mice exhibited an increase in cocaine-induced place preference compared with wild-type mice, suggesting that activation of mGlu2 receptors has a more important role than mGlu3 receptors in inhibiting the effects of drug-associated contexts and cues (Morishima et al, 2005). In addition, LY379268 blocked amphetamine-induced hyperactivity in wild-type and mGlu3 knockout mice, but not in mGlu2 knockout mice, indicating that mGlu2 receptors are required for the ability of LY379268 to attenuate the behavioral effects of psychostimulants (Woolley et al, 2008). Nevertheless, because knockout mice likely undergo compensatory changes, and LY379268 acts on both mGlu2 and mGlu3 receptors, conclusively determining which of the two mGlu receptors (mGlu2 or mGlu3) have a more important role in blocking the combined effects of nicotine and a nicotine-associated context on NAcc shell dopamine in these studies is difficult.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, mGlu2 receptor knockout mice exhibited an increase in cocaine-induced place preference compared with wild-type mice, suggesting that activation of mGlu2 receptors has a more important role than mGlu3 receptors in inhibiting the effects of drug-associated contexts and cues (Morishima et al, 2005). In addition, LY379268 blocked amphetamine-induced hyperactivity in wild-type and mGlu3 knockout mice, but not in mGlu2 knockout mice, indicating that mGlu2 receptors are required for the ability of LY379268 to attenuate the behavioral effects of psychostimulants (Woolley et al, 2008). Nevertheless, because knockout mice likely undergo compensatory changes, and LY379268 acts on both mGlu2 and mGlu3 receptors, conclusively determining which of the two mGlu receptors (mGlu2 or mGlu3) have a more important role in blocking the combined effects of nicotine and a nicotine-associated context on NAcc shell dopamine in these studies is difficult.…”
Section: Discussionmentioning
confidence: 98%
“…This is contrasted by other studies on mGluR2/3, which did not observe age- (2009) showed, however, when, using subtype specific antibodies, a higher expression of mGluR2 than mGluR3 in the dlPFC of healthy controls. In animal studies on mGluR2 and mGluR3 receptor knock-out mice, it was additionally found that mGluR2 rather than mGluR3 mediate the actions of the therapeutically active mGluR2/3 receptor agonist LY379268 (Woolley et al 2008); indicating that the mGluR2 is more likely to be involved in the therapeutic efficiency in schizophrenia pathology. We therefore used a protocol favouring binding to mGluR2 over mGluR3 (Richards et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Of course, an alternate conclusion is that the LY agonists may be ineffective in the mGlu2 KO mice because they act through mGlu2. However, the action of the LY drugs were only reported for phencyclidine doses of 3 and 5 mg/kg, but not at the maximum effective dose of 10 mg/kg phencyclidine (Fell et al, 2008;Woolley et al, 2008).…”
Section: Resultsmentioning
confidence: 99%